Occurrence of human infection with Salmonella Typhi in sub-Saharan Africa - Kim, Jong-Hoon; Parajulee, Prerana; Nguyen, Thuy Tien; Wasunkar, Shreeya; Mogasale, Vittal; Park, Se Eun; Panzner, Ursula; Mogeni, Ondari D.; Im, Justin; Marks, Florian (Scientific data, 2024)
Typhoid fever, caused by Salmonella enterica serovar Typhi, results in over 1.2 million cases and 29 thousand deaths annually from sub-Saharan Africa. Combating this disease requires various intervention approaches, such as typhoid conjugate vaccines and improving water, sanitation, and hygiene. Enhancing the effectiveness of these strategies necessitates a deeper understanding of the variation of the typhoid fever across the target region. Although the magnitude and variation of typhoid fever at the country level have been studied globally, sub-national variation remains underexplored. To address this gap, we collected data from 229 published reports on typhoid fever occurrences in sub-Saharan Africa between January 2000 and December 2020. The dataset includes information on the year and geographical location of observation, diagnostic tests used, and the type of studies in which typhoid fever was reported. By analyzing this dataset, we can gain insights into the sub-national heterogeneity of typhoid fever’s burden in the region. This knowledge will be instrumental in designing more effective intervention strategies to combat the disease.
Gesehen am 20.05.2025